Effects of live feed, artificial and mixed diet on the survival and growth of Clarias gariepinus larvae in recirculating aquaculture system - Shabdin, Mohd Long; Nor Yasmin, Kasim; Lee, Nyanti (2012)
The use of nematodes Panagrellus redivivus, dry diet and brine shrimp Artemia salina as feed for african catfish (Clarias gariepinus) larvae was tested in recirculationg aquaculture system. African catfish larvae were fed with nematode (100 ind./mL/day), brine shrimp (10 nauplii/mL/day) and dry diet, or the combination of live feeds with dry diet twice daily. The main objective was to determine the acceptability of free-living nematode in catfish larvae at first feeding.